Oblique Retro-Aortic Left Renal Vein and its Clinical Importance - Bhagavath, P.; Nayak, B.S.; Monteiro, N.P.F.; Kumar, G.P. (Kathmandu University Medical Journal, 2017)
Kidneys are the organs that remove the waste products of the metabolic activities. A smooth blood flow to the kidneys is essential to maintain their function. Abnormalities of the renal vasculature may result not only in impairing the renal function but can lead to conditions like varicocele. During an autopsy of an adult male, we observed renal vascular variations. The left renal vein had a retro-aortic course before its termination into the inferior vena cava. It was joined with the inferior vena cava at the level of inferior mesenteric artery with an acute angle. The left testicular vein joined the left renal vein with an acute angle. The right kidney was supplied by two renal arteries. The knowledge about retro-aortic course of the left renal vein may be important during renal transplantation. The oblique course of left renal vein and the termination of left testicular vein into it with an acute angle may increase the chances of left sided varicocele.